Treatment of adolescent girls with abnormal uterine bleeding taking into account psychoemotional and vegetative status - Tuchkina, I. A.; Tuchkina, M. Yu.; Novikova, A. A. (Journal of Education, Health and Sport, 2019)
The study, which was conducted at the clinical bases of the Department of Obstetrics, Gynecology and Pediatric Gynecology of the Kharkov National Medical University for 2 years, included 98 adolescent girls with abnormal uterine bleeding during puberty (AUBDP) 11-18 years old. A comprehensive clinical and laboratory examination included an analysis of complaints and the clinical course of the disease, a study of early history with an assessment of the infectious index, the course of pregnancy and labor in mothers, the degree of physical and sexual development, the characteristic of menstrual function, gynecological status, ovarian function. Also were studied urine and bacteriological seeding from the vagina, coagulogram, hormonal profile and ultrasound. The psychoemotional state of adolescents was studied using techniques adapted to their age. When treating 30 adolescent girls with AUBDP (I group), we used conservative therapy. Hormonal treatment was carried out according to strict indications of 18 adolescent girls with AUBDP (group II), with the ineffectiveness of symptomatic therapy. 50 patients with AUBDP (group III) received therapy, including medicines that contains indole-3-carbinol tranexamic acid and received physiotherapy. The established causes of bleeding, identified during the history taking, were stressful situations - 36.7%, increased physical and mental stress - 15.3%, acute and chronic respiratory and viral diseases - 12.2%. Differential use of the developed complexes of adequate therapy, taking into account the level of anxiety of patients with AUBDP, according to the indications was effective in most patients. The inclusion of physiotherapeutic treatment in therapeutic regimens helped to reduce the medicine load on the developing organism of adolescent girls. In most patients, there was an improvement in the characteristics of psychoemotional status; positive dynamics of the progress of the puberty period, normalization of menstrual function were observed. From this point of view, the active use of modern clinical diagnostic and new medical complexes using effective treatment schemes for correcting pathological conditions in adolescence is promising.